Effectiveness of Mathematical Modules with Guided Discovery Approach Viewed from PGSD UAD Student Motivation and Achievement - A Mardati (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The aim of the study was to determine the effectiveness of product development in the form of mathematical modules with a guided discovery approach in terms of motivation and learning achievement of UAD PGSD students. Guided discovery approach is a method that involves students in an optimum way to find formulas and theorems, while educators provide guidance to students who have difficulty. This type of research is a quasi-experimental study with pretest-posttest nonequivalent comparison-group design. The group used in this study consisted of two groups, namely the experimental group and the control group. Based on the calculation in the attachment, the value of t count is 5.37. The calculated t value obtained is greater than ttable = t0.05; 28 = 1.701 so Ho is rejected. Thus it can be concluded that at the 5% significance level, approach is the guided discovery effective in terms of student learning achievement. Based on the calculation in the attachment, the value of t count is -1.805. The calculated t value obtained is smaller than ttable = 1.701 so Ho is not rejected. Thus it can be concluded that at the 5% significance level, approach is the guided discovery not effective in terms of student learning motivation. It can be concluded that mathematics learning with a guided discovery approach is effective in terms of student learning achievement, but is not effective in terms of student learning motivation.